Designing Scientific Journals: Issues and Survey Results - King, William R.; Kilmann, Ralph H.; Sochats, Kenneth (Management Science, 1978)
The design parameters of scientific journals are important policy choices for journal editors as well as for the professional areas which they represent. The editorial structure of a journal presents a set of choices which importantly affect the variety of papers which are published, those that are submitted, and to some degree, the nature of future research in an area. These elements, in turn, affect reader satisfaction, journal subscriptions, and the future viability of sponsoring professional societies. This paper presents a conceptual structure for the journal-design problem and a set of survey results which should aid in addressing journal design issues and policy questions. The purpose of the paper is to define the issues and to present data in a manner that will stimulate discussion and further analyses.